α-GENERALIZED-CONVERGENCE THEORY OF L-FUZZY NETS AND ITS APPLICATIONS - Chen, Bin (Italian Journal of Pure and Applied Mathematics, 2010)
The convergence theory not only is an signi¯cantly basic theory of fuzzy topology and fuzzy analysis but also has wide applications in fuzzy inference and some other aspects. In this paper, we introduce the concept of α-generalized-remote-neighborhood of fuzzy points and establish the Moore-Smith α-generalized-convergence theory of L-fuzzy nets. Then, we introduce and study the concept of L-fuzzy α-generalized-irresolute mappings and L-fuzzy α-generalized compactness. Also we discuss the applications of α-generalized-convergence of L-fuzzy nets.